IN VIVO ENRICHMENT OF THE LAMB OF ESSENTIAL TRACE ELEMENTS FOR ITS USE IN THE TECHNOLOGY OF FUNCTIONAL FOODS - Tatiana M. Giro; Ivan F. Gorlov; Marina I. Slozhenkina; Sergey V. Kozlov; Nogman V. Tasmuchanov (Теория и практика переработки мяса)
To provide preventive measures for solving the problem of micronutrient deficiency, a new effective biologically safe method of enrichment lamb through the intervention of the cattle rations with feed supplements containing iodine and selenium in organic form has been developed. An increase in the iodine, selenium and zinc content in meat of the test animals fed enriched diets was noted, with more significant localization of elements to be registered in the meat from the ram lamb fed the «Yoddar-Zn» feed supplement together with organic selen preparation «DAFS-25» (Zn - 980 mg/100g; Se — 53.9 mg/100 g; I — 77.6 mg/100 g). So, 100 g of m. longissimus dorsi contained 8.2; 77.0 and 51.7 % of the recommended daily intake of these elements, respectively, that proved the feasibility of further output of the functional products with balanced essential nutrients. Based on the data on greater localization of microelements in meat from the ram lamb fed «Yoddar-Zn» with «DAFS-25», we made jerked snacks from the raw materials obtained from the animals of this test group. In processing, the zinc content in the product decreased by 21.3 %, iodine — 26.5 %, selenium — 16.3 % and made 771 mg/100 g, 39.72 mg/100 g, and 57.01 mg/100 g, respectively, that met the daily norm for 6.4; 56.7 and 38.0 % (for 100 g of product). In the vacuum-packed snacks, the loss of zinc was 11.3 %, iodine — 14.3 %, selenium — 12.6 % from the original content. After 3 months of storage, the zinc content in 100 g of the finished products was 5.7; selenium — 49.6; iodine — 32.6 % of the daily requirement. Investigations of physiological effect of the jerked snacks on the body of the laboratory animals were performed. Stimulating effect of selenium and iodine on the hematopoietic function of the experimental animals was revealed. The study of the functional activity of the thyroid gland found that the experimental animals’ content of thyroid stimulating hormone in blood serum was significantly higher than that of the control rats.